2020
DOI: 10.1093/humrep/deaa073
|View full text |Cite
|
Sign up to set email alerts
|

Maternal plasma genome-wide cell-free DNA can detect fetal aneuploidy in early and recurrent pregnancy loss and can be used to direct further workup

Abstract: STUDY QUESTION Can maternal plasma cell-free DNA (cfDNA) detect chromosomal anomalies in early pregnancy loss (EPL) and recurrent pregnancy loss (RPL)? SUMMARY ANSWER Genome-wide cfDNA testing can serve as an alternative to cytogenetic analysis in products of conception (POCs) in RPLs and can guide further management. WHAT IS KNOWN ALREADY Random chromosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 31 publications
4
38
1
Order By: Relevance
“…This study correctly identified 59% of chromosomal abnormalities with a 75% concordance to POC results. In comparison, Clark-Ganheart et al [6] had 87.5% concordant results where there was an available cytogenetic result, and Yaron et al [7] had 82% concordant results using pregnancy loss-specific LLR thresholds. Using 50 cases as a training set, Yaron et al [7] established a pregnancy loss-specific LLR threshold.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…This study correctly identified 59% of chromosomal abnormalities with a 75% concordance to POC results. In comparison, Clark-Ganheart et al [6] had 87.5% concordant results where there was an available cytogenetic result, and Yaron et al [7] had 82% concordant results using pregnancy loss-specific LLR thresholds. Using 50 cases as a training set, Yaron et al [7] established a pregnancy loss-specific LLR threshold.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, the miscarriages in our study cohort were diagnosed earlier than in other studies. Clark-Ganheart et al [6] recorded gestational ages of 16.9 (6.1-37.2) weeks, and Yaron et al [7] recorded gestational ages 9.6 (5.1-13.6) weeks (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations